Diffusion and Consolidation of Slag-Based Geopolymer for Concrete Pavement Rehabilitation - Wenjie Li; Jinchao Yue; Bin Liang (Applied Sciences)
Homogenized micro-crack crushing is an optimal rehabilitation technology for concrete pavement; however, when there are weak road base issues, some measures need to be taken to treat the diseases. Grouting is a common technique for addressing weak road base issues. This study developed a new visual indoor grouting test system to analyze the diffusion and consolidation of slag-based geopolymer slurry. The reactants of the geopolymer and the consolidation state of the slurry and aggregate were observed. Moreover, the reinforcement effect of the slurry on a weak road base was studied through the on-site grouting and excavation of the test pit. The results show that, during indoor grouting tests, as the size of the aggregate decreases, the slurry diffusion depth gradually decreases: only 9.5–4.75 mm aggregate formed a complete cylindrical specimen. In the tests of unformed cylindrical specimens, the 9.5–4.75 mm aggregate will develop 20–50 mm splitting surfaces, while the 4.75–2.36 mm aggregate will develop slurry bulbs and veins of different sizes, but the development is not obvious in the 2.36–1.18 mm aggregate. Fine aggregate grouting will exhibit the pressure filtration effect—especially for the 2.36–1.18 mm aggregate, the pressure filtration effect is the most obvious. An SEM microstructural analysis demonstrated that the geopolymer with a water–slag ratio of 0.4 has a faster hydration and dissolution, which results in a decrease in the density of local reactants. However, the polymerization of geopolymers is more complete. The pores of the coarse aggregate are larger and the slurry filling is denser, while the pores of the fine aggregate are smaller and the consolidation is loose locally. The consolidation of aggregates has cracks at local locations, but the width of the cracks is relatively small. On-site grouting applications revealed that the geopolymer slurry filled the bottom voids of pavement slabs and deep gaps in the road base layers, and the average deflection of the driveway decreased from 104.8 (0.001 mm) to 48 (0.001 mm) after grouting. Weak road base conditions were successfully treated, leading to a significant improvement in bearing capacity.